EDUCATION 5.0 THROUGH THE “DOCÊNCIA DIFERENTE” APP: : INNOVATION IN EDUCATIONAL TECHNOLOGY AND SCIENCE TEACHING (Interdisciplinary Studies Journal, 2025)
Education 5.0, which integrates technologies and innovative educational methodologies, can be enhanced through the “Docência Diferente” app. This application offers a range of gamified educational tools, access to the university's academic system, a website, and a YouTube channel, enabling the integration of digital technologies in the classroom and the use of apps as educational resources. In addition, innovative teaching is promoted through the implementation of active methodologies, whether in the field of Natural Sciences or Pure and Applied Mathematics. The lack of investment in school infrastructure and insufficient teacher training for the use of educational technologies are challenges to be overcome, and the “Docência Diferente” app contributes to addressing these issues by providing examples of how to use apps as digital educational resources and methodological pathways to facilitate the integration of technology into teaching practice.
Keywords: Teaching; Application (App); Education